Brain–behavior relationships in source memory: Effects of age and memory ability. (June 2017) - Meusel, Liesel-Ann; Grady, Cheryl L.; Ebert, Patricia E.; Anderson, Nicole D.
Abstract: There is considerable evidence for age-related decrements in source memory retrieval, but the literature on the neural correlates of these impairments is mixed. In this study, we used functional magnetic resonance imaging to examine source memory retrieval-related brain activity, and the monotonic relationship between retrieval-related brain activity and source memory accuracy, as a function of both healthy aging (younger vs older) and memory ability within the older adult group (Hi-Old vs Lo-Old). Participants studied lists of word pairs, half visually, half aurally; these were re-presented visually in a scanned test phase and participants indicated if the pair was 'seen' or 'heard' in the study phase. The Lo-Old, but not the Hi-Old, showed source memory performance decrements compared to the Young. During retrieval of source memories, younger and older adults engaged lateral and medial prefrontal cortex (PFC) and medial posterior parietal (and occipital) cortices. The groups differed in how brain activity related to source memory accuracy in dorsal anterior cingulate cortex, precuneus/cuneus, and the inferior parietal cortex; in each of these areas, greater activity was associated with poorer accuracy in the Young, but with higher accuracy in the Hi-Old (anterior cingulate and precuneus/cuneus) and Lo-Old (inferior parietal lobe). Follow-up pairwise group interaction analyses revealed that greater activity in right parahippocampal gyrus was associated with better source memory in the Hi-Old, but not in the Lo-Old. We conclude that older adults recruit additional brain regions to compensate for age-related decline in source memory, but the specific regions involved differ depending on their episodic memory ability.